Adolescents' knowledge, attitudes and behaviour regarding HIV/AIDS in Valhalla Park: an exploratory study - Isaacs, Conrad Henry (University of the Western Cape, 2014)
Magister Artium - MA === In South Africa there is still a substantial amount of prejudice towards people living with Aids (PLA). Initially, Aids was seen as a 'gay' disease, then a 'black' disease. People thus tended to avoid high-risk groups rather than high-risk behaviour, and denied their own vulnerability by displacing the disease to an 'other' who did not belong to 'their' group. This study focuses on factors that influence and motivate adolescents' behavior towards HIV/AIDS at Beauvallon High School in Valhalla Park; an impoverished, peri-urban and previously coloured only community. === South Africa